Pengaruh Penggunaan Gagdet terhadap Hasil Belajar Siswa Kelas XII MIPA SMAN 5 Model Palu pada Mata Pelajaran Biologi - Aprilya, Dinda; Masrianih, Masrianih; Trianto, Manap (BIO-EDU: Jurnal Pendidikan Biologi, 2024)
Gadgets are small electronic devices that have special functions to download the latest information. The use of gadgets is not only limited to the entertainment aspect, but has also penetrated into the world of education, especially among students. This study aims to describe the effect of gadget use on the learning outcomes of students of class XII MIPA SMAN 5 Model Palu in Biology subject. This type of research is descriptive quantitative. The sample in this study were XII MIPA class students of SMAN 5 Model Palu as many as 55 students using purposive sampling technique. Data collection techniques using questionnaires and documentation. Data analysis techniques were performed with normality test, simple linear regression test and F test. The results showed that there is a positive influence of gadget use on student learning outcomes at SMAN 5 Model Palu. Through hypothesis testing with the F test, the f-table is obtained at 4.02 so that f-count = 28.238> f-table = 4.02 which means it has a significant effect.